Media Strategies in Dealing with the African Union Against Military Coups in the African Continent: An Analytical Study for the Period (2019-2023): Mali, Niger, and Burkina Faso as a model (The International Journal for Scientific Research, 2025)
Africa is the second-largest continent after Asia in terms of area and population. It is a vast landmass through which the equator roughly passes, and most of its regions lie between the Tropic of Capricorn and the Tropic of Cancer. For this reason, it is often referred to as “Tropical Africa.” The African continent is also considered part of the Old World. What has further increased the strategic importance of media in the African continent is the growing advancement in monitoring the two surrounding oceans—the Atlantic Ocean to the west and the Indian Ocean to the east. Africa’s coastlines are characterized by the absence of significant indentations, bays, or peninsulas, which contributed to the establishment of a chain of natural ports suitable for shipping vessels. These coasts also served as the main routes connecting the interior of the continent to the outside world. All of this has led to the emergence of Africa’s strategically important geographic position, overseeing the transportation routes that link the East and the West. Over time, the strategic significance of this geographical position has further increased in the field of international relations.In this research, the author addresses the military coups in Mali, Niger, and Burkina Faso as examples of military coups in the African continent. The phenomenon of military coups has been one of the major challenges faced by the African Union since its establishment, prompting it to formulate a media strategy to deal with this issue. Media strategies, therefore, represent a process of alignment and adaptation between an organization’s operations and its core activities to achieve competitive advantage. These strategies are also widely used concepts in the social, political, military, and economic sciences, referring to more than one meaning. Essentially, they involve determining long-term objectives. The strategic media vision in dealing with the African Union regarding military coups in Africa firmly rejects any form of military takeover and emphasizes the preservation of democracy and the legitimacy of lawful governance in all African states.
Keywords: Strategies; Media; African Union; Military Coups; African Continent